Utilization of YAP:Ce powder scintillator for 57Fe Mössbauer spectroscopy. (December 2021) - Kočiščák, Jan; Procházka, Vít; Novák, Petr
Abstract: Using a powder scintillator for a detection of gamma and X-rays allows to create detectors of various shapes, moreover the handling and fabrication of such scintillators is much easier than in the case of large or thin monocrystals. We report on the application of YAlO 3 :Ce powder to Mössbauer spectroscopy. The detection efficiency and the energy resolution of the scintillators made of powders of two different granularities (grain size ≤ 30 μ m and 50– 70 μ m ) were investigated. The powder scintillators exhibited a comparable energy resolution and detection efficiency as YAlO 3 :Ce monocrystal with thickness of 400 μ m . Burying the YAlO 3 :Ce grains into the epoxy resin increased the energy resolution of powder scintillators. The studied scintillators were found to be suitable for experiments in Mössbauer spectroscopy. The performance of YAP is also compared to the NaI:Tl scintillator. Graphical abstract: Highlights: Yap:Ce powder exhibits comparable detection efficiency as YAP:Ce monocrystal. Covering YAP:Ce powder with epoxy resin increases its energy resolution and mechanical hardness. YAP:Ce powder is efficient for a photon detection in Mössbauer spectroscopy. Scintillation crystals of various shapes could be made from YAP:Ce powder.